Organizational learning and purchase-supply relations in Japan Hitachi, Matsushita and Toyota compared - Lincoln, James R. (California management review)
This article deals with the role of purchase-supply relations in organizational learning and knowledge-creation in Japana and how such relations are currently undergoing change. Drawing on interviews with managers, it presents case studies of the customer-supplier partnerships of three prominent Japanese manufacturing firms : Hitachi, Matsushita and Toyota. The Hitachi case illustrates in a somewhat novel way the prevailing paradigm of how long-term, high-trust supply relations in Japan enhance organizational knowledge creation, learning and innovation. The Toyota and Matsushita cases demonstrate that the dynamics of learning are behind two very different kinds of change in keiretsu supply networks. Toyota's evolving relationship with long-term partner, Denso Corporation, appears to fit the popular view that globalization and technological change are eroding Japanese keiretsu ties. The Matsushita case, by contrast, demonstrates that these same forces of change in other industrial settings may in fact be strengthening keiretsu-style partnerships.